La prensa sefardí en Rumanía: contenidos del periódico El Luzero de la Pasensia (Turnu-Severin 1885-1888) - Martínez-Gálvez, Cristina (Revista de Filología Románica, 2009)
Balkans published more than two hundreds newspapers, most of them stamped on aljamia (Spanish written in Hebrew characters). Nevertheless, in this study we will pay attention to El Luzero de la Pasensia, a Sephardic newspaper stamped on Latin letters in Turnu-Severin (Rumania), from November 1885 to December 1888. We will analyze its main features (structure, contents, ideology, discussions about language...) and we will make a hypothesis about the influences which could have provoked the creation of this newspaper.
Keywords: Jews; Sephardic; The Balkans; Press; El Luzero de la Pasensia